2009
DOI: 10.1021/ja902143w
|View full text |Cite
|
Sign up to set email alerts
|

α′-Hydroxyenones as Mechanistic Probes and Scope-Expanding Surrogates for α,β-Unsaturated Aldehydes in N-Heterocyclic Carbene-Catalyzed Reactions

Abstract: N-heterocyclic carbene catalyzed reactions of α,β-unsaturated aldehydes and a variety of electrophiles allow the facile preparation of a diverse array of annulation products including trisubstituted cyclopentenes, γ-lactams, and bicyclic β-lactams. The substrate scope of these reactions, however, is limited by the difficulties of preparing the startingα,β-unsaturated aldehydes. We now report that α′-hydroxyenones, which can be prepared in a single convenient step from aromatic and heteroaromatic aldehydes, can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
96
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(100 citation statements)
references
References 63 publications
0
96
0
4
Order By: Relevance
“…178 A limitation is that the increased steric demand of these substrates inhibits their use with bulky chiral catalysts. In 2013, Chi and co-workers demonstrated that saturated esters are potential homoenolate precursors.…”
Section: Catalysis Involving Extended Breslow Intermediatesmentioning
confidence: 99%
See 1 more Smart Citation
“…178 A limitation is that the increased steric demand of these substrates inhibits their use with bulky chiral catalysts. In 2013, Chi and co-workers demonstrated that saturated esters are potential homoenolate precursors.…”
Section: Catalysis Involving Extended Breslow Intermediatesmentioning
confidence: 99%
“…178,206 A wide variety of aromatic and heteroaromatic substituents are tolerated as reaction partners for annulation with vinylogous amides. The product 3,4-dihydropyridinones are isolated in good-to-excellent yields (59–99%).…”
Section: Catalysis Involving Acylazolium Intermediatesmentioning
confidence: 99%
“…Benzalacetone (2a) and dibenzalacetone (2d) were prepared according to Golodnikov and Mandel'shtam [16]. Treatment of -benzoylacrylic [(2E)-4-oxo-4-phenylbut-2-enoic] acid [17] with thionyl chloride and subsequent addition of excess methanol gave the corresponding methyl ester 2e [18]. The ethyl ester of (Z)-2-benzylidene-3-oxobutanoic acid 2f was prepared according to Anaç et al [19].…”
Section: Methodsmentioning
confidence: 99%
“…Intramolecular ester formation with the release of NHC catalyst yields a bicyclic adduct VII containing a four-membered b-lactone. Spontaneous decarboxylation [36][37][38][39] and oxidation [40][41][42] of VII effectively affords benzene product bearing four substituents in predictable substitution patterns. Decarboxylation of b-lactone fused with a six-membered ring similar to intermediate VII is a highly effective process, as exemplified in Lupton's [4 þ 2] reaction via carbene catalysis 39 .…”
mentioning
confidence: 99%